Transnational activism, Amnesty International and human rights in China: the implications of consistent civil and political rights framing - Fleay, Caroline (Routledge, 2011)
This article explores Amnesty International's consistent focus on civil and political rights in its campaigning on China. Such a focus has been evident from the beginning of Amnesty International's attention to human rights in China in the late 1970s to the present, despite the decision in 2001 that the organisation would work to promote all categories of human rights. This suggests that the early framing of human rights as particular civil and political rights by the organisation continues to be a somewhat settled frame of meaning in the case of China. The implications of this framing include that while it elevates certain abuses within China, abuses that local activists face considerable domestic constraints to highlight, it inevitably marginalises other abuses and obscures more complex understandings of human rights in China.